Decrease in the resistance level of Blattella germanica (Linnaeus) (Blattodea: Ectobiidae) to insecticides after being reared without selection pressure for ten years: Penurunan tingkat resistensi Blattella germanica (Linnaeus) (Blattodea: Ectobiidae) terhadap insektisida setelah dipelihara tanpa tekanan seleksi selama sepuluh tahun - Dini, Putik Van; Hariani, Nova; Yusmalinar, Sri; Jane, Erfanus; Ahmad, Intan (Jurnal Entomologi Indonesia, 2023)
This study aims to investigate changes in resistance to insecticides over a ten-year period in five strains of German cockroaches, Blattella germanica (Linnaeus), which had previously shown resistance to deltamethrin, propoxur, and fipronil in 2012. The five strains were reared in a laboratory without exposure to insecticides for ten years. In 2022, they were tested for resistance to the same insecticides using a topical application method. The resistance ratio (RR50) was calculated for each strain to determine the level of resistance to each insecticide. The study found that German cockroaches, initially resistant, became less resistant or even susceptible after being reared in a laboratory without insecticide exposure for over ten years. This decrease in resistance was observed in all strains, but the reduction pattern varied, apparently influenced by the type of insecticide.  For instance, the MDN2 strain, which initially had a very high level of resistance (RR50: 1019.74 -fold) to deltamethrin, became susceptible (RR50: 1 -fold). Similarly, the ACH2 strain, initially classified as highly resistant to propoxur (RR50: 48.64 -fold), and the strain with high resistance (RR50: 12.21 -fold) to fipronil, both became susceptible. The study also discussed potential mechanisms for the decrease in resistance, including reduced frequency of resistance genes and fitness costs. The findings suggest that rearing German cockroaches in a laboratory without insecticide treatment can lead to a decrease in resistance to commonly used insecticides. These findings can be used to develop more effective methods for controlling German cockroaches.